SOSIALISASI TENTANG MITIGASI BENCANA ALAM DALAM KEGIATAN PERSAMI DI SMP NEGERI 3 PEUSANGAN - meilinar, fina; Muntaird, Muntadir; Zunuanis, Zunuanis; Novalita, Rahmi; Syahrin, Alfi; Maritalia, Dewi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity (PKM) aims to broaden the knowledge and understanding of students of SMP N 3 Peusangan who are members of the scout organization and become participants in the Persami about the types and character of natural disasters as well as disaster management actions and disaster mitigation principles. Socialization activities are carried out by the activity implementation team by delivering material on the type and character of natural disasters as well as disaster management actions and disaster mitigation principles. Based on the results of PKM activities that have been carried out by the Community Service team consisting of lecturers and students of the Postgraduate Social Science Education Study Program at Almuslim University, Bireuen Aceh, are as follows: 1) improve the knowledge and understanding of students of SMP N 3 Peusangan who are members of scout organizations in Persami activities about the types and character of natural disasters as well as disaster management actions and disaster mitigation principles; and 2) increasing enthusiasm of students in implementing the knowledge they learned in this program on their scouting activities, so as to create a generation that can work together in groups of organizations and individuals who are ready to face various unpredicted natural conditions.